Search for very light CP-odd Higgs boson in radiative decays of Υ(1S) - Love, W; Savinov, V; Mendez, H; Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Anderson, M; Cummings, J; Danko, I; Hu, D; et al. (2008)
We search for a non-SM-like CP-odd Higgs boson (a10) decaying to τ+τ- or μ+μ- in radiative decays of the Υ(1S). No significant signal is found, and upper limits on the product branching ratios are set. Our τ+τ- results are almost 2 orders of magnitude more stringent than previous upper limits. Our data provide no evidence for a Higgs state with a mass of 214 MeV decaying to μ+μ-, previously proposed as an explanation for 3 Σ+→pμ+μ- events observed by the HyperCP experiment. Our results constrain NMSSM models. © 2008 The American Physical Society.